A COMPARATIVE STUDY ON EFFECT OF ENDOGENOUS AND EXOGENOUS ECZEMA ON QUALITY OF LIFE - Najia Ahmed (Army Medical College Rawalpindi, 2019)
Objective: To compare the effect of endogenous and exogenous eczema on quality of life using Dermatology Life Quality Index.